Screening of advanced sugarcane genotypes against rust mite - K S, MOHAN KUMAR; SHARMA, KULDEEP; VIJAYKUMAR, L; YADAV, SURESH (The Indian Journal of Agricultural Sciences, 2021)
In the screening trial, among the nineteen sugarcane genotypes screened for the reaction to sugarcane rust mite, Abacarus sacchari, only 2 genotypes (009-64 and 0961-07) harboured >1 mites /2 cm2 leaf area while remaining all the genotypes harboured